Disturbance of oxidative balance in the first trimester of spontaneous abortions - Grujić Zorica; Grujić Ilija; Bogavac Mirjana; Nikolić Aleksandra; Mitić Radoslav; Stajić Zoran (Vojnosanitetski Pregled)
Background/Aim. Pregnancy is defined as a condition of increased oxidative stress. The aim of this research was to determine the intensity of pro-oxidative processes and the content of GSH, as well as antioxidative enzymes: superoxide dismutase (SOD), catalase (CAT), gluthatione peroxidase (GSH-Px), and the total antioxidative status (TAS) in patients with spontaneous abortions. Methods. A total of 120 patients were involved in the research (70 spontaneous abortions and 50 healthy pregnancies). The patients were divided into groups: 35 patients with incomplete and complete spontaneous abortion (group S), 35 patients with missed abortion (group M) and a control group of 50 healthy pregnancies (group N), all of them being in the first trimester of pregnancy. The intensity of lipid proxidation (LPx) was determined with a modified thyobarbituric acid method. The GSH content in erythrocytes was determined by the method ba-sed on the amount of non-protein sulfhydryl residues using the Ellman's reagens. The following antioxidative parameters in the blood were measured: SOD – by the method with xanthine oxidase-using commercial RANSOD sets; CAT – by the method of Aebi (the enzyme activity was measured by monitoring the decomposition of H2O2 at 240 nm); GSH-Px was determined using hydrogen peroxide as a substrate. The TAS was determined using the ferric reducing autioxidant potential (FRAP) met-hod. Results. The highest average value of LPx was recorded in the spontaneous abortion group (48.03 pmoL/mg Hgb), and the lowest value was recorded in the control group (26.06 pmoL/mg Hgb). A statistically significant positive correlation between LPx and CAT in the group of patients with missed abortion was also noted (p < 0.05, r = 0.37). There was a statistically highly significant difference (p < 0.001) in SOD and in CAT activitices be-tween the examined patients (groups S and N) and the control group (Student’s t-test and ANOVA). The highest average value of TAS was recorded in the group S (710.39 μmol/L), while the value in the group M was 277.66 μmol/L. The average value of TAS in the control group was 452.12 μmol/L. Student’s t-test showed a statistically highly significant difference in the values of TAS between the examined patients (groups S and M) and the control group. Conclusion. Determination of the value of pro-oxidative and antioxidative parameters in patients with sponta-neous abortion can be the indicator of condition of fetoplacental unit and these analyses can be included in the protocol of the rutine perinatal diagnostics.